Effectiveness of bedside investigations to diagnose peripheral artery disease among people with diabetes mellitus: a systematic review. (26th January 2016) - Brownrigg, J. R. W.; Hinchliffe, R. J.; Apelqvist, J.; Boyko, E. J.; Fitridge, R.; Mills, J. L.; Reekers, J.; Shearman, C. P.; Zierler, R. E.; Schaper, N. C.; ,
Abstract: Non‐invasive tests for the detection of peripheral artery disease (PAD) among individuals with diabetes mellitus are important to estimate the risk of amputation, ulceration, wound healing and the presence of cardiovascular disease, yet there are no consensus recommendations to support a particular diagnostic modality over another and to evaluate the performance of index non‐invasive diagnostic tests against reference standard imaging techniques (magnetic resonance angiography, computed tomography angiography, digital subtraction angiography and colour duplex ultrasound) for the detection of PAD among patients with diabetes. Two reviewers independently screened potential studies for inclusion and extracted study data. Eligible studies evaluated an index test for PAD against a reference test. An assessment of methodological quality was performed using the quality assessment for diagnostic accuracy studies instrument. Of the 6629 studies identified, ten met the criteria for inclusion. In these studies, the patients had a median age of 60–74 years and a median duration of diabetes of 9–24 years. Two studies reported exclusively on patients with symptomatic (ulcerated/infected) feet, two on patients with asymptomatic (intact) feet only, and the remaining six on patients both with and without foot ulceration. Ankle brachial index (ABI) was the most widely assessed index test. Overall, the positive likelihood ratio and negative likelihood ratio (NLR) of an ABI threshold <0.9 ranged from 2 to 25 (median 8) and <0.1 to 0.7 (median 0.3), respectively. In patients with neuropathy, the NLR of the ABI was generally higher (two out of three studies), indicating poorer performance, and ranged between 0.3 and 0.5. A toe brachial index <0.75 was associated with a median positive likelihood ratio and NLRs of 3 and ≤0.1, respectively, and was less affected by neuropathy in one study. Also, in two separate studies, pulse oximetry used to measure the oxygen saturation of peripheral blood and Doppler wave form analyses had NLRs of 0.2 and <0.1. The reported performance of ABI for the diagnosis of PAD in patients with diabetes mellitus is variable and is adversely affected by the presence of neuropathy. Limited evidence suggests that toe brachial index, pulse oximetry and wave form analysis may be superior to ABI for diagnosing PAD in patients with neuropathy with and without foot ulcers. There were insufficient data to support the adoption of one particular diagnostic modality over another and no comparisons existed with clinical examination. The quality of studies evaluating diagnostic techniques for the detection of PAD in individuals with diabetes is poor. Improved compliance with guidelines for methodological quality is needed in future studies.